CD 4+, CD 8+ and CD 19+cell surface antigen and abnormal mitochondria ultrastructure of peripheral blood P-type atypical lymphocytes in patients with schizophrenia. (21st April 2023) - Xu, Ruihuan; Song, Shijun; Liu, Caihong; Luo, Ruibin; Gu, Wen; Luo, Xia; Wang, Jiajian; Yang, Litao; Chen, Ribing; Chen, Huixiong; Wan, Yanbin; Hong, Xiongxin; et al.
Abstract: Objective: P-type atypical lymphocytes may play important roles in the aetiology and therapy of schizophrenia. However, there is merely a direct immunological characterisation of it. The aim of this study is to explore the surface antigens of these cells and their comparative ultrastructure in schizophrenia. Methods: We recruited 25 age-and gender-matched patients with unmedicated schizophrenia, other mental diseases and healthy individuals. Peripheral venous blood was smeared and stained. CD4+, CD8+ and CD19+ cell surface antigen- positive lymphocytes were purified using magnetic beads and prepared for light microscopy and electron microscopy. Results: The percentages of P-type atypical lymphocytes (34.53% ± 9.92%) were significantly higher ( p  < 0.0001) in schizophrenia than that of other mental diseases (9.79% ± 3.45%). These cells could present CD4+, CD8+ and CD19+ surface antigens. Their relative ultrastructure differed from that of normal lymphocytes, especially in mitochondria, which showed abundant, aggregated and quite irregular mitochondria; for example, slight dilation of the foci, swelling, degeneration, and even cavity. Conclusions: P-type atypical lymphocytes could be found among CD4+, CD8+, and CD19 + lymphocytes with schizophrenia. Their abnormal ultrastructure of mitochondria implied that energy metabolism might play an important role in the aetiology of schizophrenia.